EFFECT OF ROLE-PLAY AND VESTIBULE TRAINING ON EMPLOYEE PERFORMANCE IN SELECTED HOTELS IN KADUNA STATE, NIGERIA - Yakubu, Keturah; Zwingina, Christy (African Journal of Social and Behavioural Sciences, 2025)
In this age of technological advancement, change is a recurring and persistent factor. As a result, organizations must ensure that training is consistent to tackle the challenges that arise from political, financial, societal, and pioneering changes in the environment. This study, therefore, examined the effect of role-play and vestibule training on employee performance in hotels in the Kaduna metropolis. Data were collected through a structured questionnaire, which was issued to a sample of 291 employees of the hotels. Data was analysed using descriptive statistics, correlation and multiple regression techniques, which include ANOVA, model summary and co-efficient. Findings from the study show that training methods such as role play and vestibule training have significant and positive effects on employee performance. Specifically, the study revealed that role-play has a significant and positive effect (p<0.000, β = 46.6%) on the performance of employees amongst hotels in Kaduna. The study also found that vestibule training has a significant and positive effect (p<0.016, β = 14.3%) on the performance of employees in hotels in Kaduna. The study revealed that role-play training has a stronger effect on the performance of employees as compared with vestibule training. The study recommends, amongst others, that Management should stimulate training that workers require to improve their performance and capabilities, which consequently increases organizational performance as well.